ANALISIS USABILITY PADA E-LEARNING MENGGUNAKAN METODE 10 HEURISTICS EVALUATION (STUDI KASUS : LEARNING ACTIVITIES THROUGH DIGITAL SYSTEM (LEADS) UPNVJ) - Yoel Marcelino (2023)
Through technological developments, there has been an increase in learning methods that continue to experience modernity, where one example is by using e-learning. E-learning is a learning model that utilizes websites to serve as the underlying media. Through the use of e-learning, the learning process can be carried out in a flexible time and place. The good of e-learning is indicated by an increase in the skills of the users who use it. Interface design is one of the elements that has its importance that can provide support for the quality of education in cyberspace. Jakarta Veterans National Development University (UPNVJ) has an e-Learning website known as LeADS (Learning Activities Through Digital System). The LeADS website was created with consideration in terms of User Interface and User Experience design, to make it easy for users to access academic information. In this study, a usability analysis was carried out on the LeADS website based on the Heuristics Evaluation method to determine the usability value of LeADS based on ten heuristic principles. The purpose of this study is to analyze the usability of the e-learning Learning Activities Through Digital System (LeADS) at the National Veterans Development University Jakarta, as well as provide advice to LeADS e-learning developers by recommending the results of usability evaluation tests for the system on the LeADS website.